Cerita Siswa Tentang Membaca: Refleksi Pendekatan Humanistik Dalam Membangun Minat Baca Anak - Safina Kapriyati (LPPM Institut Pendidikan Nusantara Global, 2026)
Students' reading interest at the elementary school level remains low in the digital era due to excessive exposure to digital devices, limited intrinsic motivation, and reading activities that are often perceived as compulsory academic tasks rather than enjoyable experiences. This condition highlights the need for an instructional approach that not only develops reading skills but also addresses students' emotional needs and psychological well-being. Therefore, a humanistic approach was adopted because it emphasizes respect for students' interests, needs, and individual potential, thereby fostering intrinsic motivation to read. This study aimed to explore students' subjective experiences and describe the implementation of a humanistic approach in promoting reading interest through authentic student narratives. A qualitative descriptive design was employed. Thirty-two fourth-grade students completed an initial questionnaire, after which four students and one classroom teacher were purposively selected for in-depth interviews and classroom observations. Data credibility was ensured through methodological triangulation and analyzed using the Miles and Huberman interactive model. The findings revealed that the humanistic approach enhanced students' intrinsic reading interest through five key elements: autonomy in selecting reading materials, a comfortable reading environment, teachers as reading role models, empathetic guidance, and unconditional appreciation of students' progress. The study concludes that the humanistic approach transforms reading into a meaningful and enjoyable learning experience that effectively strengthens students' intrinsic motivation to read.